International legal aspects of the sovereignty of states in the context of globalization - Kubeyev, Ye.K.; Abdakimova, M.Yu. (KSU publ., 2015)
This article deals with the theme of the sovereignty of States, which requires constant attention of researchers. This need is particularly felt in modern world of increasing interdependence of the international community. The ratio of globalization and sovereignty belongs to one of the fundamental problems of modern international relations. Intense globalization and active processes of integration, accompanied by the laying on of the states of their traditional functions and powers to international organizations in order to successfully address regional and universal problems become apparent trend of the international community.
Keywords: the sovereignty of States; globalization; international legal personality; the European Union